The Double Burden: A Bibliometric Analysis on Tuberculosis with Diabetes Mellitus Comorbidity - Machrumnizar Machrumnizar; Adang Bachtiar; Rina K. Kusumaratna (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
Many studies have been conducted independently and collaboratively to find effective ways to control TB. However, the prevalence of TB continues to increase, especially in low- and middle-income countries. This study highlights the breadth of research conducted worldwide and collaborative networks over the past decade. Between 2003 and 2023, 410 research articles on TB with comorbid diabetes were analyzed using the Scopus database, with an annual growth rate of 7.18%, reaching its peak in 2022. The keywords “tuberculosis” and “diabetes mellitus” were found to have a total link strength of 2895 and 3101, respectively. The most published articles on TB-DM were published in the International Journal of Tuberculosis and Lung Disease (23). Babu, Subash (23) authored the most TB-DM article publications. The National Institute for Research in Tuberculosis is the most productive affiliation (12), making India the country with the most published articles. Still, the Netherlands led in average article citations (32.8%), and the United States has the most collaborative link country (324). Visualization of the co-occurrence and co-authorship networks was conducted using R-Studio and VOS-Viewer. The study highlights the rising tuberculosis and diabetes incidence, identifies research trends, disparities, and bidirectional control innovations, providing valuable insights for policy recommendations.